Social Investment Market: Kuhn meets New Institutionalism – framing an emerging field - Nummela, Tomi (2012)
This study sees Social Investment Market (“SIM”) as an emerging field and surveys the relevant sector and theoretical literature to investigate the paradigmatic development of the market and to suggest institutional theory as valid research framework. UK market development and current stage is outlined and used as a background to illustrate the themes in the study. Market is summarised and followed as the flow from supply level investor decisions to demand level actors delivering social impact. Market continuum is consolidated into a holistic concept of SIM. Kuhnian observations on paradigm development are used in order to assess the market as science and as an emerging field of practice. New institutional theory context is suggested as the most relevant framework for the emerging field study and institutional entrepreneurship is introduced as one potential explanatory avenue to outline the institutional factors in play within the field.